El presupuesto ejecutado y el número de servicios brindados por el centro de innovación productiva y transferencia tecnológica de Maynas – cite productivo Maynas en el periodo 2019 – 2023 - Sánchez Elaluff, Cynthia Ludy (2025)
The work of the Productive Innovation and Technology Transfer Centers (CITEs Productivos) is fundamental to substantially improving the productivity and competitiveness of local businesses. It responds to a government policy and has been established in the main provinces. The Maynas Productive CITE operates in the province of Maynas. This doctoral-level research studies the relationship between institutional budget execution and the number of services provided during the 2019-2023 period. The historical development of the variables is used, making this thesis quantitative; at the same time, it is correlational because it examines the existence of associations between the variables. The data were organized as shown in the data source, making the design non-experimental. The conclusion is that there is no association between the variables (r = -0.190488332). The executed budget was approximately 87.66% of the allocated budget, amounting to S/. 9,587,794.00; demonstrating that spending efficiency needs to be adjusted. The most requested service by users was Specialized Technological Information, having been provided 13,594.00 times, representing 76.51% of the total. The type of client that most requested the institution's services was Entrepreneurs, having requested 4,072.00 services, equivalent to 55.79% of the total.